Construction of radicalism and communication in groups that are considered radical - Alfarabi; Suminar, Panji (Jurnal Studi Komunikasi, 2022)
This study aims to determine the conditions that encourage the construction of radicalism in Bengkulu and how it affects the formation of communication patterns in the SS group who are considered exposed to radicalism. The theory used to understand the formation of the narrative of radicalism is the construction of social reality from Berger and Luckman. The research method uses a constructivist paradigm with a case study approach. Data collection techniques using interviews, observation, and literature review. The results of the study found that the construction of radicalism in the SS group was formed by two factors– the first was the SS group's rejection of long-standing community traditions such as tahlilan, grave pilgrimage, and yasinan; the second is the factor of the mass media showing terrorist actors who use the same symbols as the symbols worn by the SS group. The impact of the radicalism label is that the communication formed in the SS group is exclusive, while the village community applies one-way communication in understanding the SS group.